2002
DOI: 10.1177/0093650202029003005
|View full text |Cite
|
Sign up to set email alerts
|

Person-Effects and Heuristic-Systematic Processing

Abstract: The study explores the relationship between heuristic and systematic processing and first-, second-, and third-person effects. Controversy surrounding a referendum over the Confederate battle emblem appearing on the Mississippi state flag served as a backdrop for a survey of residents (N = 520) concerning the perceptions of the media's influence on self and others. Results suggest that accuracy-motivated heuristic and systematic processing shows a limited relationship to third-and first-person effects while at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…This is what this study aims to do. One of the most plausible explanations offered by social psychologists and political scientists is that people tend to simplify the decision-making process and heavily rely on heuristics, motivated reasoning, as well as wishful thinking, especially when their knowledge on the subject is sparse (Kahneman et al 1982;Zaller 1992;Lau and Redlawsk 2001;Kuklinski et al 2001;Neuwirth et al 2002). Dolan and Holbrook (2001) have aptly described the debate about the sources of public opinion as the role of affect versus cognition in the formation of perceptions.…”
Section: Economic Perceptions In Central and Eastern Europementioning
confidence: 99%
“…This is what this study aims to do. One of the most plausible explanations offered by social psychologists and political scientists is that people tend to simplify the decision-making process and heavily rely on heuristics, motivated reasoning, as well as wishful thinking, especially when their knowledge on the subject is sparse (Kahneman et al 1982;Zaller 1992;Lau and Redlawsk 2001;Kuklinski et al 2001;Neuwirth et al 2002). Dolan and Holbrook (2001) have aptly described the debate about the sources of public opinion as the role of affect versus cognition in the formation of perceptions.…”
Section: Economic Perceptions In Central and Eastern Europementioning
confidence: 99%
“…While no direct studies of people's actual behavior has been conducted, several studies have found third person effects in connection with opinions on censorship and freedom of expression issues. In general, strong support for the perceptual component of the theory has been demonstrated but only limited support exists for the behavioral component (Johansson, 2002, Neuwirth et al 2002.…”
Section: First and Third Person Effectsmentioning
confidence: 99%
“…The reason for excluding political authority from the model is that it tends to covary with job type, thus the inclusion of both tends to weaken the explanatory power of the model. Also included in the model is a control variable known in the third person effects literature as second person effects (Neuwirth et al 2002). This variable takes into account the degree of influence the media has both on one self and others and therefore allows for a certain 'levelling' of the influence of the media often missing in third person effects studies.…”
Section: Politicians and Third Person Effectsmentioning
confidence: 99%
See 2 more Smart Citations